Serum Magnesium: A Forgotten Electrolyte after Total Thyroidectomy - Muhammed, Adi Syazni; Abdullah Suhaimi, Shahrun Niza; Lee, Qi Zheng (IIUM Medical Journal Malaysia, 2021)
Hypocalcemia is a common complication after total thyroidectomy; however, hypomagnesemia is also frequently detected, and its role is often disregarded. We report a 72-year-old woman who underwent total thyroidectomy with neck dissection and subsequently developed atrial fibrillation due to hypocalcemia and hypomagnesemia. The pathophysiology of hypomagnesemia after total thyroidectomy and its significance in calcium homeostasis is described.